2021
DOI: 10.1177/19322968211023806
|View full text |Cite
|
Sign up to set email alerts
|

Inspecting Insulin Products Using Water Proton NMR. I. Noninvasive vs Invasive Inspection

Abstract: Background: There is a clear need to transition from batch-level to vial/syringe/pen-level quality control of biologic drugs, such as insulin. This could be achieved only by noninvasive and quantitative inspection technologies that maintain the integrity of the drug product. Methods: Four insulin products for patient self-injection presented as prefilled pens have been noninvasively and quantitatively inspected using the water proton NMR technology. The inspection output is the water proton relaxation rate R2(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The R 2 ( 1 H 2 O) values have been successfully measured on unopened vials, which could then be used for clinical purposes. 44 w NMR has been successfully applied to quality control on oils and oxidation-induced perturbations in the formation of fibrin clots; however, to our knowledge, this technology has not been applied to monitoring forced degradation mAb-based therapeutics. In this context, it has great potential due to simple and rapid nature of the measurement, with one R 2 ( 1 H 2 O) measurement taking only approximately 50 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…The R 2 ( 1 H 2 O) values have been successfully measured on unopened vials, which could then be used for clinical purposes. 44 w NMR has been successfully applied to quality control on oils and oxidation-induced perturbations in the formation of fibrin clots; however, to our knowledge, this technology has not been applied to monitoring forced degradation mAb-based therapeutics. In this context, it has great potential due to simple and rapid nature of the measurement, with one R 2 ( 1 H 2 O) measurement taking only approximately 50 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the turbidity of the sample does not influence the sample analysis. To date, it has been utilized in numerous biopharmaceutical-related studies, such as to investigate the gene filling of adeno-associated viral capsids, monitor vaccine adjuvant filling level, and sedimentation kinetics, in addition to the inspection of biologic product vials. With respect to proteins, w NMR has been used to monitor the oxidation of a mAb in real time, as well as to obtain information about solution protein concentration under both static and flow conditions, with sensitivity shown to concentrations as low as 0.4 mg mL –1 . Taraban et al have also demonstrated that R 2 ( 1 H 2 O) is sensitive to protein aggregates with a size smaller than 0.45 μm and showed that it was capable of outperforming SEC, DLS, and microflow imaging .…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration of water in biopharmaceuticals and vaccines (~ 90% and above, over 50 M) allows monitoring of the 1 H 2 O signal using compact low-field benchtop NMR relaxometers with a wide bore which can accommodate a drug product in the original container. Hence, all analyses are done noninvasively and do not compromise a drug product which can still be used after measurement, including for patient administration [25]. Data collection is fast (from several seconds to 1-2 min at most), and data analysis is straightforward, easily automatable, and does not require high-level expertise.…”
Section: Introductionmentioning
confidence: 99%